2020
DOI: 10.1038/s41598-020-58332-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes and cognitive function at baseline in the Brazilian Longitudinal Study of Adult Health (ELSA- Brasil)

Abstract: Diabetes has been associated with cognitive changes and an increased risk of vascular dementia andAlzheimer's disease, but it is unclear whether there are associations between diabetes and early alterations in cognitive performance. The present study consisted of a cross-section analysis of 14,444 participants aged 35-74 years and from a developing country at baseline in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil); these participants were recruited between 2008 and 2010. We investigated whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 47 publications
5
34
0
6
Order By: Relevance
“…A recent study has reported that metabolic conditions such as type 2 diabetes and obesity are directly linked to cognitive impairment in the central nervous system (CNS) 4 . In addition, one study has demonstrated that patients with type 2 diabetes and obesity experience accelerated memory loss and impaired verbal fluency compared to normal subjects 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported that metabolic conditions such as type 2 diabetes and obesity are directly linked to cognitive impairment in the central nervous system (CNS) 4 . In addition, one study has demonstrated that patients with type 2 diabetes and obesity experience accelerated memory loss and impaired verbal fluency compared to normal subjects 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic imbalance leads to chronic inflammation, insulin resistance, oxidative stress, vascular damage, and impaired lipid and glucose metabolism in the systemic circulation and CNS 6 . These may contribute to changes in brain function and metabolic stress in the body 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Teixeira et al confirmed an association between diabetes and cognitive performance, mainly in the domains of memory, attention, concentration, psychomotor speed and executive function. 38 Hewitt et al reported that insulin-dependent older persons with cognitive impairment had poorer knowledge about managing hypoglycemia and medications than did patients without impairment. 31 Patients with poor glycemic control lacked understanding of basic self-care (mechanisms of medications, concepts of glucose monitoring, symptom detection, role of exercise, dietary instructions, and behavior-lifestyle adjustment), and had difficulty detecting and solving problems.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic imbalance leads to chronic inflammation, insulin resistance, oxidative stress, vascular damage, and impaired lipid and glucose metabolism in the systemic circulation and CNS 6 . These may contribute to changes in brain function and metabolic stress in the body 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent study has reported that metabolic conditions such as type 2 diabetes and obesity are directly linked to cognitive impairment in the central nervous system (CNS) and metabolic problems 4 . In addition, one study has demonstrated that patients with type 2 diabetes and obesity experience accelerated memory loss and impaired verbal fluency compared to normal subjects 5 .…”
Section: Introductionmentioning
confidence: 99%